KEANEKARAGAMAN IKAN (PISCES) DI DANAU LEBAR SUOH KABUPATEN LAMPUNG BARAT SEBAGAI SUMBER BELAJAR BIOLOGI MATERI KEANEKARAGAMAN HAYATI BERUPA ENSIKLOPEDIA - Handoyo Handoyo; Handoko Santoso; Rasuane Noor (EDUBIOLOCK, 2023)
The aims of this study were (1) to find out what types of fish (Pisces) are found in Lebar Suoh Lake, West Lampung Regency. (2) Knowing the index of fish diversity (Pisces) found in the Lebar Suoh Lake, West Lampung Regency. (3) Develop learning resources in the form of encyclopedias. The research was conducted with a qualitative approach, the research used was descriptive. The sampling technique used purposive sampling technique. Sampling using fishing gear Bubu, fishing rods, and nets. The results of research that has been carried out in Lake Lebar Suoh, West Lampung, found 15 species belonging to 10 families. The species found were Osphronemus goramy L., Barbonymus gonionotus B., Oreochromis mossambicus L., Osteochilus hasselti V., Pangasius hypopthalmus S., Mystus nemurus V., Bagrus nemurus V., Rasbora pavie T., Macrognathus aculeatus B., Trichogaster trichopterus P., Anabas testudineus B., Clarias gariepinus B., Channa striata B., Aplocheilus panchax H., Oreochromis niloticus L. The most species was Osteochilus haseselti V. with a total of 148 individuals belonging to the family Cyprinidae, while the least species was Macrognathus aculeatus B. with a total of 40 individuals belonging to the family Mastacembelidae. The research that has been done is then used in learning resources in the form of encyclopedias, learning resources in the form of encyclopedias get validation from design and material expert validators. The validation results get an average score of 95%, which means that the quality criteria of the encyclopedia are very valid to be used. Osphronemus goramy, Barbonymus gonionotus.